Revival of Legacy of Tooke and Gibson: Further Evidence and Implications for Monetary Policy - Atiq-ur-Rehman (Journal of Central Banking Theory and Practice, 2017)
Traditional economics assumes that interest rate effects inflation by changing the aggregate demand (Barth and Ramay, 2002). On the other hand, many economists in recent years have explored the cost side effects of monetary transmission and found very strong evidences in favour of cost channel. One of such studies is that by Rehman (2015) which explores the relationship between interest rate and inflation for a large data set comprising various measures of interest rate and inflation from countries around the globe. Rehman (2015) computes the correlation between two variables and he finds that the correlation between two variables is either positive or insignificant. Rehman argues that the finding is quite robust and does not change with a change in measure of interest rate and/or inflation. If the correlation between interest rate and inflation is positive then using interest rate to control inflation would be counterproductive. Thus it will endorse the warning of Wright Patman, a US congressman and Chairman of Joint Economic Committee who argues that "senseless of trying to fight inflation by raising interest rate, throwing the gasoline on fire to put out the flames would be as logical". Findings of Rehman (2015) are based on correlation coefficients. The correlation without having control variables could only provide a clue and could be subject to serious missing variable bias. However, Rehman (2015) argues that thousands of similar clues from the entire globe collectively become very strong evidence. However, given the importance of the topic, it is necessary to do a more careful analysis and summarize the relationship between two variables which is not subject to missing variable bias. Therefore, this paper applies more sophisticated econometric techniques including Granger Causality and Static Long Run Solution to find the impact of interest rate and inflation.
Keywords: E40; E42; E52; 330; Cost Channel; Gibson Paradox; Tooke Banking School Theory; Monetary Transmission Mechanism; Monetary Policy Effectiveness.